Social perceptions influencing the fight against Covid-19 in Cote D’Ivoire - Tchétché, Mathieu Obou (Open Science Journal, 2021)
In a context of new outbreak of the Covid-19 after a phase of control, the problem of influence of perceptions of professional and community actors on the epidemiological riposte arises in Africa and particularly in Côte d'Ivoire. Indeed, the main question is how could strengthening community involvement contribute to resilience against Covid-19 in Côte d'Ivoire? The study is based on a mixed method that combines quantitative and qualitative approaches. Quantitatively, it involves exploiting the daily statistics on Covid-19 in Côte d'Ivoire. The qualitative aspect requires the analysis of official, administrative, audio-visual and iconographic documents supplemented by investigations within a collective intelligence network and among a population of men and women in bus stations, markets and supermarkets in Cocody, Yopougon and Abobo in the city of Abidjan. 166 people were interviewed. The results show that an organizational framework for the epidemiological riposte exists in Côte d'Ivoire with the multi-sector riposte plan as its anchor. Statistics related to this struggle show that after six months, more and more recoveries occur as new cases are confirmed. Likewise, active cases and deaths have a downward trend. Despite an acceptable score, some populations perceive the organization of the fight as centralized, infiltrating initiatives at the operational level by excluding community health workers; and others perceive it as a finding for those in power to benefit from Covid funds from the international community. All of these perceptions have a negative influence on the conduct of the epidemiological riposte and community involvement. This is characterized by the slackening of the involvement of certain professional and social actors in the fight, the non-respect of hygienic and social distancing measures, as well as difficulty in determining the originality of national resilience.